Factors for Decreasing Cholinesterase Enzyme Activity in Farmers in Trimurdjo District, Central Lampung Regency - Yusmutia, Annisa; Meita Mahardianti; Tiwi Lestari (RADINKA JAYA UTAMA PUBLISHER, 2023)
Blood cholinesterase level is the amount of active cholinesterase enzyme in blood plasma and red blood cells. Early detection of pesticide poisoning is by checking the cholinesterase enzyme in the blood. The purpose of this study was to determine the factors affecting cholinesterase enzyme activity in farmer groups in the Trimurdjo district and Central Lampung district. This study uses quantitative research that uses a cross-sectional approach, and the subject of this research is the farmers of Trimurjo District, Central Lampung, as many as 86 farmers. The results showed that there was a significant relationship between cholinesterase enzyme activity and nutritional status variables, pesticide doses, and the highest risk obtained was the variable use of personal protective equipment (PPE) (PR = 0.205, 95% CI = 0.048 - 0.866) in farmers in Trimurjo District, District of Trimurjo Regency. Central Lampung has been controlled by confounding variables. The results showed that the activity of the cholinesterase enzyme in farmer groups who used pesticide doses that were not under SOP (Standard Operating Procedures), did not use personal Protective Equipment (PPE) when spraying, and had poor nutritional status had a higher risk of experiencing pesticide poisoning or cholinesterase enzyme activity. low. Efforts that can be made to reduce the number of farmers experiencing pesticide poisoning or low cholinesterase enzyme activity are by conducting counseling by related sectors.